Stahl's essential psychopharmacology : neuroscientific basis and practical applications - Stahl, Stephen M. 1951-; Muntner, Nancy (Cambridge, United Kingdom Cambridge University Press, 2013)
With this fully revised fourth edition, Dr Stahl returns to the essential roots of what it means to become a neurobiologically empowered psychopharmacologist, expertly guided in the selection and combination of treatments for individual patients in practice. Embracing the unifying themes of 'symptom endophenotypes', dimensions of psychopathology that cut across syndromes, and 'symptoms and circuits', every aspect of the text has been updated to the frontiers of current knowledge, with the clarity of explanation and illustration that only Dr Stahl can bring. Integrating much of the basic neuroscience into the clinical chapters, and with major additions in the areas of psychosis, antipsychotics, antidepressants, impulsivity, compulsivity and addiction, this is the single most readily readable source of information on disease and drug mechanisms. This remains the essential text for all students and professionals in mental health seeking to understand and utilize current therapeutics, and to anticipate the future for novel medications
Keywords: Psicofarmacología; Neurociencias; Neurobiología